The AHL Quorum-Sensing System Negatively Regulates Growth and Autolysis in Lysobacter brunescens - Ling, Jun; Zhou, Lan; Wu, Guichun; Zhao, Yancun; Jiang, Tianping; Liu, Fengquan (Frontiers in Microbiology, 2019)
Lysobacter species are emerging as novel sources of antibiotics, but the regulation of their physiological metabolism is still poorly understood. In this work, we extracted AHL (acyl-homoserine lactone) autoinducers, identified the structures of AHLs and described the AHL quorum-sensing system in Lysobacter brunescens OH23. AHLs were isolated from the supernatant of L. brunescens OH23, and ESI-MS/MS (electrospray ionization mass spectrometry) analysis revealed biosynthesis of three different AHL chemical structures by L. brunescens OH23: N-(3-oxohexanoyl)- homoserine lactone (HSL), 3-OH-C10-HSL and C8-HSL. The growth rate of AHL quorum-sensing knockout mutants was dramatically increased compared to that of wildtype. Sucrose consumptions were also twice as high in AHL quorum-sensing knockout mutants than that in wildtype in early-log phase. Additionally, expression of key genes related to sucrose metabolism α-glucosidase was enhanced in AHL quorum-sensing knockout mutants, which indicated that AHL quorum sensing negatively regulates sucrose uptake and metabolism which further affects the growth rate of L. brunescens. Furthermore, autolysis was strongly induced in AHL quorum-sensing knockout mutants compared to wildtype, suggesting that AHL quorum sensing plays a negative regulatory role in cell autolysis. Moreover, compared to wildtype, XSAC (Xanthomonas-specific antibiotic compound) production was significantly increased in AHL knockout mutants in the early-log and late-log phases, and surface motility capabilities are also enhanced also in AHL knockout mutants; the normalized data of XSAC production and surface motility and expressions of key genes related to these two phenotypes reveal that growth rare and autolysis strongly affects XSAC biosynthesis and surface motility rather than AHL quorum-sensing system. Our results show that the AHL quorum-sensing system negatively regulates cell growth and autolysis, and further maintain nutrition homeostasis and population stability in L. brunescens.